2020
DOI: 10.17063/bjfs9(4)y2020440-458
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric Determination of LSD with a Schiff Base – Chemically Modified Electrode in Aqueous Solution

Abstract: In recent years, practical, inexpensive, and highly specific electroanalytical methods based on modified electrodes have been increasingly developed for forensic science. Simple modification of the carbon paste electrode with Schiff base complexes has become a promising strategy to detect and quantify narcotics. In this context, we aimed to develop voltammetric methods to quantify lysergic acid diethylamide (LSD) by using a carbon paste electrode modified with the complex [UO2(Ac-ophen)]·H2O. The use of an aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…[46][47][48] Recently, these complexes have also been employed as carbon paste electrodes to detect LSD. 49 As part of our ongoing research on Schiff bases and transition metal compounds, 3,[46][47][48][49][50][51][52][53][54][55]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[46][47][48] Recently, these complexes have also been employed as carbon paste electrodes to detect LSD. 49 As part of our ongoing research on Schiff bases and transition metal compounds, 3,[46][47][48][49][50][51][52][53][54][55]…”
Section: Introductionmentioning
confidence: 99%
“…46–48 Recently, these complexes have also been employed as carbon paste electrodes to detect LSD. 49…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,24–28 With all electrodes printed on the same substrate, SPEs can analyze minimal sample volumes (50 to 100 μL) and have been successfully utilized to determine different application, 26,29,30 including illicit drugs. 31–35 To the best of our knowledge, among the electroanalytical methods reported for LSD detection, 25,36–38 only one study employing SPE with a graphite working electrode has been found. 25…”
Section: Introductionmentioning
confidence: 99%
“…19,[24][25][26][27][28] With all electrodes printed on the same substrate, SPEs can analyze minimal sample volumes (50 to 100 mL) and have been successfully utilized to determine different application, 26,29,30 including illicit drugs. [31][32][33][34][35] To the best of our knowledge, among the electroanalytical methods reported for LSD detection, 25,[36][37][38] only one study employing SPE with a graphite working electrode has been found. 25 Different carbonaceous nanomaterials, such as graphite (SPE-Gr), graphene (SPE-GP), single-wall carbon-nanotubes (SPE-SWCNT), and multi-wall carbon-nanotubes (SPE-MWCNT), can be used as working electrodes on SPE and are widely used in electroanalytical applications.…”
Section: Introductionmentioning
confidence: 99%